P^3x+p^2y-p^2x-py=0, where p=dy/dx
Given equation is: "p^3x+p^2y-p^2x-py=0"
"p^2x(p-1) + py(p-1) = 0"
"p(p-1)(px+y) = 0"
Solving it we get, "p=0,p-1 = 0, px+y=0"
Then, for "p = 0, \\implies \\frac{dy}{dx} = 0"
Integrating it we get, "y = c_1" (1)
where c1 is constant.
For p-1=0,
"\\frac{dy}{dx} -1= 0"
"\\int {dy} =\\int dx"
"y = x + c_2" (2)
For px+y = 0,
"x\\frac{dy}{dx} + y= 0"
"x\\frac{dy}{dx} = -y"
"\\frac{dy}{y} = -\\frac{dx}{x}"
integrating both sides,
"\\ln y = -\\ln x + \\ln c_3"
"y = \\frac{c_3}{x}" (3)
Equations (1), (2), and (3) are the solutions of the differential equation.
Comments
Leave a comment